Hydrothermal Synthesis and Characterization of Europium-doped Barium Titanate Nanocrystallites - García-Hernández, Margarita; Chadeyron, Geneviève; Boyer, Damien; García-Murillo, Antonieta; Carrillo-Romo, Felipe; Mahiou, Rachid (Nano-Micro Letters, 2013)
Barium titanate nanocrystallites were synthesized by a hydrothermal technique from barium chloride and tetrabutyl titanate. Single-crystalline cubic perovskite BaTiO3 consisting of spherical particles with diameters ranging from 10 to 30 nm was easily achieved by this route. In order to study the influence of the synthesis process on the morphology and the optical properties, barium titanate was also prepared by a solid-state reaction. In this case, only the tetragonal phase which crystallizes above 900° was observed. High-temperature X-ray diffraction measurements were performed to investigate the crystallization temperatures as well as the particle sizes via the Scherrer formula. The lattice vibrations were evidenced by infrared spectroscopy. Eu3+ was used as a structural probe, and the luminescence properties recorded from BaTiO3:Eu3+and elaborated by a solid-state reaction and hydrothermal process were compared. The reddish emission of the europium is increased by the nanometric particles.